AB0749 Ultrasound detected pathotology of the metatarsophalangeal joints in rheumatoid arthritis: association with pain and functional disability. (23rd January 2014) - Osipyants, R.; Karateev, D.; Panasyuk, E.; Smirnov, A.; Lukina, G.; Glukhova, S.; Alexandrova, E.; Volkov, A.; Nasonov, E.
Abstract : Background: Investigation of the feet is not included in the disease activity score-28 (DAS 28), the most widely used instrument to measure disease activity in rheumatoid arthritis (RA). This can lead to false results when determining the clinical remission and can cause the underestimation of disease activity. Objectives: To examine the relationship between ultrasound (US)-detected pathology in the metatarsophalangeal (MTP) joints, pain and physical function in patients with RA. Methods: Patients with RA [N=36, median age 51 (range 43-57) years; disease duration 54 (24-96) months; DAS28-CRP 3.9 (2.2-4.6)] were included in this study. All patients were assessed for clinical disease activity: presence or absence of swelling and/or tenderness in the MTPjoints and visual analogue scale (VAS) assessments (0-100) for the patient's global assessment of health and disease activity. US was performed by a single operator, unaware of clinical data ("Voluson-i" (GE, USA) with transducer (4-13MHz)). B-mode US was done in the accessible aspects of the second through fifth MTPjoints of the feet. Each joint was scored according to the OMERACT definitions of pathology [1 ]. The US and clinical examinations were performed on the same day. Radiography was performed within 4-6 weeks of the other evaluations. Data on physical function were collected using the Health Assessment Questionnaire Disability Index (HAQ). Results: Evaluation by US indicated signs of synovitis in 36 patients, while clinical examination revealed signs of inflammation in 30 patients [100 vs. 83%, p<0.01]. Erosive disease was identified in 35 patients by US, compared with 30 cases by radiography [97 vs. 83%, p<0.05]. Thirty-three of 36 patients (92%) had functional disability. Patients with mild to severe disability (HAQ>1) were older [54 (46-59) vs. 45 (37-52) years, p<0.04] and had higher levels of pain (increase in pain VAS) [70 (50-75) vs. 45 (30-50) mm, p<0.01], than those who had less functional disability. Also the same tendency was observed to US signs of synovitis in MTP 5 th [70 vs. 38%, p=0.07] and the number of painful MTP (defined as a tender joints count) [91 vs. 69%, p<0.09]. There were no significant differences in US score of structural damage, X-ray – erosions of the feet or laboratory data and clinical disease activity markers as well as disease duration between patients with or without the impairment of physical function. Conclusions: This study confirmed the higher sensitivity for US examination in detecting synovitis and structural damage and demonstrated that pain, age and the presence of US-detected inflammationin the MTP joints (MTP 5 th ) contributed to poorer physical function in patients. Examination of the foot joints by US may be of major clinical importance in RA. References: Wakefield RJ, Balint PV, Szkudlarek M, Filippucci E, Backhaus M, D'Agostino M et al. Proceedings from the OMERACT Special Interest Group for Musculoskeletal Ultrasound including definitions for ultrasonographic pathology. J Rheumatol 2005; 32:2485-7. Disclosure of Interest: None Declared